The blockade of NMDA receptor ion channels by ketamine is enhanced in developing rat cortical neurons - Jin, Jianhui (2013)
Ketamine is a non-competitive antagonist of NMDA receptors (NMDARs) commonly used as a dissociative anesthetic in many pediatric procedures. Ketamine acts primarily by blocking NMDA ligand-gated channels. Experimental studies indicate that ketamine administration used for inducing clinically relevant anesthesia can lead to neurotoxic effects, such as apoptosis, selectively on immature brain neurons. However, the underlying mechanisms remain unclear. This study used whole-cell patch-clamp recordings in an in vitro preparation of forebrain slices to analyze pharmacologically the differences in the effects of ketamine administration on the NMDAR channel activity between immature and mature neurons. NMDAR channel activity was recorded in the form of evoked NMDAR-mediated excitatory postsynaptic currents (eEPSCs) from the forebrain of both neonatal and adult rats. Results show that ketamine inhibited eEPSCs in a dose-dependent manner in both immature and mature neurons. However, at each concentration of ketamine applied to the brain slice, a more extensive inhibition could be seen in neonatal neurons than in adult neurons. Further, the blocking effect of ketamine on eEPSCs was measured during the period of 1, 3, and 6 h after ketamine washout. Inhibition of eEPSCs in immature neurons was still evident 6 h after washout. In contrast, the blockade of eEPSCs in mature neurons recovered completely from the inhibition by ketamine in a time-dependent manner. These results indicate that ketamine produces a greater and longer blocking effect on NMDAR channels in immature neurons than in mature neurons. This differential effect is likely to be a critical link to the higher vulnerability to ketamine-induced neurotoxicity in neurons of the developing brain.